COVID-19 in Patients With Seizures and Epilepsy: Interpretation of Relevant Knowledge of Presenting Signs and Symptoms. Issue 5 (September 2020) - Hogan, Robert Edward; Grinspan, Zachary; Axeen, Erika; Marquis, Belinda; Day, B. Keith
There are an increasing number of clinical studies for COVID-19, with several large cohort studies documenting initial signs and symptoms. Realizing the need for current information, this summary provides a focused summary of pertinent clinical diagnostic information about neurological involvement of SARS-CoV-2 virus and clinical presentation of COVID-19, especially in relationship to patients with seizures and epilepsy. There is no evidence from cohort studies in the general population that seizures are worsened in COVID-19. However, relative lack of cohort studies in patients with a history of epileptic seizures limit conclusions about effects of COVID-19 patients with epilepsy. Overall, findings indicate seizures and epilepsy are rare, especially in mild COVID-19 cases, but may occur in more severe cases later in the disease course. Caregivers should be vigilant in assessing for possible seizures, especially in patients with systemic effects of severe COVID-19 infections.